Run-Time Discovery, Selection, Composition & Invocation of Web Services using Semantic Descriptions - Brady, Colm (Trinity College Dublin. Department of Computer Science, 2004)
Web Service computing is enabled by using an architecture that provides interoperability between disparate and diverse applications. One goal of Web Services is to facilitate inter-organisational distributed computing using traditional protocols such as the Hyper Text Transfer Protocol (HTTP) and the Simple Mail Transfer Protocol (SMTP). However, these web service technologies do not provide standards for dynamically discovering, selecting candidates, composing and invoking Web Services based on their capabilities. In effect, a human must interpret the functionality or applicability of a web service and write some software capable of using the service or configure a generic client to invoke the service. Industry is currently proposing several standards which allow for software Agents to automate the process of composing Web Services, by annotating Web Services capabilities in machine readable form and using reasoners to reason over this information. OWL-S is an emerging XML based mark-up language that can be used to describe the non-functional and functional attributes of a Web Service. OWL-S provides a well defined framework for expressing the capability of Web Services, in a platform and technology neutral representation. This Dissertation is concerned specifically with researching the OWL-S specification for semantic mark-up of Web Services. Of specific interest are methods and techniques to use OWL-S descriptions for semantic discovery incorporating non-functional service attributes, candidate selection, service composition and semantic service invocation.
Keywords: Computer Science